Hubungan Sikap dan Posisi Kerja dengan Low Back Pain pada Perawat Di RSUD Purbalingga - Fatoni, Himawan; Handoyo,; Swasti, Keksi Girindra (Jurnal Keperawatan Soedirman, 2009)
Low back pain is one of musculoskeletal disorder that is caused by inappropriate body activity. Several factors that contribute towards low back pain are age, obesity, body mass index and pregnancy. However, the most contributing factor toward low back pain is inappropriate position during activity. Some nurses’ activities also have potentially risk towards low back pain for example during lifting their patients and performing activity at operation room The purpose of this research is to show whether the correlation of job posture and position with low back pain by the nurses of Regional Hospital of Purbalingga The research was descriptive analysis with cross sectional approach. Of 32 respondents fulfilling inclusion criteria were chosen through purposive sampling method. The variable of the research was job posture and position as the independent variable and low back pain as dependent one. The research instrument was Ovako Working Posture Analysis System (OWAS) for testing job posture and position, meanwhile laseque test was tool for testing low back pain. Chi Square statistic test was used to show the correlation of job posture and position with low back pain. The result shows that 10 respondents have job posture and position that was possible for causing musculoskeletal injuries and 6 respondents were suffering low back pain. Chi Square statistic test results ?2count = 1,208, the value was lower than ?2table for ? = 0.05 which is 3.841, thus it was concluded that there was not correlation between job posture and position with low back pain. There was not correlation between job posture and position with low back pain suffered by the nurses of Regional Hospital of Purbalingga